Code Switching and Code Mixing on EFL Students’ Whatsapp Chatting Group - Yuliana Dg. Macora (Sintuwu Maroso Journal of English Teaching, 2019)
There are 37 data Inter-sentential switching, 63 data of Intra-sentential switching, 10 data of Emblematic/tag switching, 4 data of Intra-word switching, and 8 data of Establishing continuity with the previous speaker. Then 46 data of Intra-sentential mixing, 57 data of Intra-lexical mixing, and 30 data of Involving a change of pronunciation. While for the reason of doing code switching and code mixing, the reason of real lexical need is the most frequently occur by the members that happen 35 times in the data. It is supported by the interview result that the members did the code switching and code mixing, because they mostly need real lexical need and due to the lack of equivalent lexicon in Bahasa language. Also some words are more intimate to say to a close friend, more suitable in current situation, and more widely use in daily conversation. If the word or sentence put into Bahasa, the meaning will be hazy/vague, and sometimes it would not suitable